Origin of the Shang between Mythology and Inscriptions - XǓ , Jǐnjīng (Estudios Complutenses de Asia Oriental, 2025)
Every civilization in the world has its own splendid myths. Of course, these legends are not created out of thin air, but are further processing and sublimation of the distant history of the ancient ancestors of their own civilization. The second dynasty in Chinese history was founded by Tāng around 1600 B. C. and was destroyed by the zhōu in 1046 B. C. This dynasty was already known through the records in the later classical books, and, in the year 1899, the discovery of the bone inscriptions of the Shāng dynasty has allowed us to access the first-hand data of the time. But if we make a comparison between the traditional records and the Shāng records, we can find several discrepancies. In this article, we will compare the records related to the origin of the Shāng in the traditional records such as Chronicles of the great historian, classic of Mountains and Seas, Elegies of Chǔ, etc., with the contemporary inscriptions of the Shāng dynasty and some information obtained through archeaology to see if they are consistent or contradictory.